2021
DOI: 10.3389/fmed.2021.697804
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil NETworking in ENL: Potential as a Putative Biomarker: Future Insights

Abstract: Erythema nodosum leprosum (ENL), also known as type 2 reaction (T2R) is an immune complex mediated (type III hypersensitivity) reactional state encountered in patients with borderline lepromatous and lepromatous leprosy (BL and LL) either before, during, or after the institution of anti-leprosy treatment (ALT). The consequences of ENL may be serious, leading to permanent nerve damage and deformities, constituting a major cause of leprosy-related morbidity. The incidence of ENL is increasing with the increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 113 publications
(84 reference statements)
1
5
0
Order By: Relevance
“…Macrophages, which are tissue monocytes, are the main resident cells activated by M. leprae infection [ 6 , 16 ]. Earlier studies indicated that ENL patients experienced a greater release of TNF-α from monocytes upon contact with M. leprae [ 12 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Macrophages, which are tissue monocytes, are the main resident cells activated by M. leprae infection [ 6 , 16 ]. Earlier studies indicated that ENL patients experienced a greater release of TNF-α from monocytes upon contact with M. leprae [ 12 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Histological studies showed an intense perivascular infiltrate of neutrophils throughout the dermis and subcutis, especially within 72 h of ENL onset [ 11 , 12 ]. The circulating neutrophils appeared to contain M. leprae bacilli, albeit in the absence of systemic inflammation [ 16 ]. Neutrophilic degranulation was observed in ENL, with a subsequent high production of low-density neutrophils [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This data is suggestive of NETs contributing towards more severe leprosy disease. A recent review discusses the potential for NETs as a putative prognostic tool in ENL to direct medical treatment ( 177 ).…”
Section: Neutrophil Extracellular Trap-mediated Killing Of Mycobacteriamentioning
confidence: 99%
“…Although the mechanisms that trigger the reaction and the crucial pathways linked to the inflammatory response are still elusive, neutrophils are recognized as key players during ENL ( 13 , 14 ). Early histological studies revealed a rich neutrophilic infiltrate in cutaneous ENL lesions ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%